English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-07-03 13:19:00 · 5 answers · asked by Poetry 1 in Science & Mathematics Mathematics

5 answers

ym(xm-xmy^2)
=ym{xm(1-y^2)
=(ym)(xm)(1+y)(1-y)
=xym^2(1+y)(1-y)

2007-07-03 13:24:19 · answer #1 · answered by alpha 7 · 0 0

ym(xm – xmy^2) = x y (1-y) (1+y) m^2

2007-07-03 13:27:50 · answer #2 · answered by oregfiu 7 · 0 0

Factor xm out

ym*xm(1-y^2)

yxm^2(1-y^2)

Difference of squares.

yxm^2(1+y)(1-y)

2007-07-03 13:24:35 · answer #3 · answered by UnknownD 6 · 0 0

ym(xm-xmy^2=ymxm(1-y^2)=m^2xy(1+y)(1-y). answer

2007-07-03 13:23:55 · answer #4 · answered by Anonymous · 0 0

= ym.[ xm (1 - y²)]
= (ym).(xm).(1 - y).(1 + y)
= x.y.m² (1 - y).(1 + y)

2007-07-07 00:15:43 · answer #5 · answered by Como 7 · 0 0

fedest.com, questions and answers